Odpowiedź :
1) Tak
[tex](3^2)^7=9^7\\9^3*9^4=9^{3+4}=9^7[/tex]
2) Tak
[tex]4^8:4^3=4^{8-3}=4^5\\2*2^4*2^5=2^{1+4+5}=2^{10}=(2^2)^5=4^5[/tex]
3) Nie
[tex]\sqrt[3]{-57} :\sqrt[3]{-3} =\sqrt[3]{19}[/tex]
4) Nie
[tex]3\sqrt{28} =3\sqrt{4*7} =3*2\sqrt{7} =6\sqrt{7}[/tex]
Pozdrawiam.
[tex](3^2)^7=9^3\cdot9^4\\9^7=9^7\\\text{TAK}\\\\4^8:4^3=2\cdot2^4\cdot2^5\\4^5=2^{10}\\(2^2)^5=2^{10}\\2^{10}=2^{10}\\\text{TAK}\\\\\sqrt[3]{-57}:\sqrt[3]{-3}=-\sqrt[3]{19}\\\sqrt[3]{-57:(-3)}=-\sqrt[3]{19}\\\sqrt[3]{19}\neq-\sqrt[3]{19}\\\text{NIE}\\\\3\sqrt{28}=12\sqrt7\\3\sqrt{4\cdot7}=12\sqrt{7}\\3\cdot2\sqrt7=12\sqrt7\\6\sqrt7\neq12\sqrt7\\\text{NIE}[/tex]